Mengembangkan Pemahaman Etika Melalui Ajaran Brahmacari Asrama Di Panti Asuhan Ananda Seva Dharma - Kadek Sita Devi (Pramana: Jurnal Hasil Penelitian, 2023)
Being born as a human is a beautiful gift because humans are called the most perfect creatures. In Hinduism, humans are said to be the most perfect creatures because they have Idep, which means the ability to think. Good thoughts can also help develop human education related to ethics, especially since understanding ethics is very important for humans. One way to control thoughts and develop an understanding of ethical education is by studying. In Hinduism, the learning stage is called the Brahmacari period, in which this activity involves learning not only in terms of formal education, but also in terms of non-formal education which can shape human character and ethics.